Hepatitis E seroprevalence in a German cohort of patients with inflammatory bowel diseases - Hoffmann, Peter; Behnisch, Rouven; Gsenger, Julia; Schnitzler, Paul; Gauss, Annika (PLOS ONE, 2020)
Background and aims The incidence of hepatitis E virus (HEV)-infections in industrialized nations has been increasing over the past years. Patients suffering from inflammatory bowel diseases (IBD) may be more prone to transmission. Data on HEV seroprevalence in IBD patients is scarce and has not been reported in German IBD patients. The German Health Examination Survey for Adults 2008-2011, which included 4.422 samples, found a HEV seroprevalence of 16.8%, increasing with age. The aim of the present study was to determine the seroprevalence of anti-HEV IgG in a German cohort of IBD patients, and to explore which parameters have an impact on HEV seroprevalence. Material and methods This is an uncontrolled, cross-sectional, retrospective monocentric study. Among the patients visiting the IBD outpatient clinic between 25 January, 2019 and 24 September, 2019, 328 patients with Crohn’s disease (CD) and 150 patients with ulcerative colitis (UC) were included in the study. IgG antibodies against HEV were determined by enzyme-linked immunosorbent assay. Positive antibody titers were verified using immunoblot analysis. Medical records were reviewed for demographic and clinical parameters to identify potential risk factors for HEV infection. Results The prevalence of anti-HEV IgG antibodies was 17.4% in CD patients and 24.7% in UC patients. No patient with positive HEV PCR was detected. Greater age of CD und UC patients and longer duration of anti-interleukin 12/23 treatment in CD patients were associated with higher anti-HEV IgG antibody rates. Conclusions In summary, we conclude that patients with UC have a higher anti-HEV IgG antibody prevalence than the general population in Germany, and that immunosuppressive therapy may carry no higher risk for HEV infection.